Análise da importância do sebo bovino para produção de biodiesel utilizando a análise pestal e swot com a escala likert - Sousa, Sidney Soares de (Universidade Federal do Tocantins, 2021)
The central theme of this study is bovine tallow, a residue from the agribusiness that is used, among other uses, in the production of biodiesel, being the second most used raw material in the production of this biofuel in Brazil. Based on this condition, this study sought to analyze the importance of beef tallow in the Brazilian biodiesel production market, using an Environmental Scanning of the macro and micro environmental factors that involve the residue as an agroenergetic raw material. The research was exploratory, with a qualitative approach, and used the bibliographic procedure, basing the analysis on studies and reports on the subject. And for environmental scanning, the PESTAL analysis was used, which involves the political, economic, social, technological, environmental fields. With this reading, the SWOT analysis was used to survey the opportunities and threats of PESTAL factors, as well as the strengths and weaknesses of bovine tallow as a biodiesel feedstock. From this, the strengths and weaknesses were crossed with the opportunities and threats, using scores based on the Likert Scale. With the crossover, the strategic posture of beef tallow as development was determined, due to the predominance of opportunities and strengths. And based on the posture identified, and considering that it allows an offensive action of bovine tallow, it was concluded that the creation of an organized and stable national market is preponderant, allowing the increased participation of this raw material in the production of biodiesel given its importance in this market. The conclusion is justified in five major advantages identified: (a) the great availability of the raw material linked to beef production, (b) the low cost of tallow, (c) the percentage of conversion into oil, (d) the non-competition with food, and (e) the correct destination for an industrial waste of great environmental impact.